1998
DOI: 10.1111/j.1469-7793.1998.653bs.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion permeation and conduction in a human recombinant 5‐HT3 receptor subunit (h5‐HT3A)

Abstract: A human recombinant homo‐oligomeric 5‐HT3 receptor (h5‐HT3A) expressed in a human embryonic kidney cell line (HEK 293) was characterized using the whole‐cell recording configuration of the patch clamp technique. 5‐HT evoked transient inward currents (EC50= 3.4 μM; Hill coefficient = 1.8) that were blocked by the 5‐HT3 receptor antagonist ondansetron (IC50= 103 pM) and by the non‐selective agents metoclopramide (IC50= 69 nM), cocaine (IC50= 459 nM) and (+)‐tubocurarine (IC50= 2.8 μM). 5‐HT‐induced currents rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
87
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 29 publications
(80 reference statements)
18
87
0
1
Order By: Relevance
“…Noise Analysis-Single channel conductances were determined using nonstationary variance analysis (20). Whole cell patch-clamp recording was performed at room temperature using an Axopatch 1D or 200B (Axon Instruments) amplifier.…”
Section: Methodsmentioning
confidence: 99%
“…Noise Analysis-Single channel conductances were determined using nonstationary variance analysis (20). Whole cell patch-clamp recording was performed at room temperature using an Axopatch 1D or 200B (Axon Instruments) amplifier.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological data support the suggestion that the charged groups line portals within the sides of the ICD, and influence the ion flux between the cytoplasm and the inner vestibule at the base of the pore (Miyazawa et al 1999 ;Unwin, 2000). As the widest region of the portals resembles the diameter of a hydrated permeant ion, they provide an explanation for the homomeric 5-HT 3 channel having a much smaller unitary conductance than most nAChRs, despite their similar ionic permeabilities and very similar M2 sequences (Brown et al 1998 ;Lambert et al 1989 ;Malone et al 1991 ;Mochizuki et al 2000 ;Yakel et al 1990 ;Yang, 1990). Additional studies have shown that the conductance of the channel can be dynamically altered by sulphydryl modifying reagents (Deeb et al 2007) and the permeability of divalent cations is also altered by mutations in this region (Livesey et al 2008).…”
Section: Channel Conductancementioning
confidence: 99%
“…The effects of these ions vary according to the receptor type and subunit composition. For example, in the a7 nAChR, these cations potentiate responses, while 5-HT 3 R responses are typically reduced (Brown et al 1998;Hu & Lovinger, 2005 ;Niemeyer & Lummis, 2001 ;Thompson & Lummis, 2008a). Ionbinding sites in many Cys-loop receptors have been identified in the channel (Bertrand et al 1993 ;Eddins et al 2002aEddins et al , 2002bGill et al 1995 ;Hu & Lovinger, 2005 ;Livesey et al 2008 ;Niemeyer & Lummis, 2001 ;Noam et al 2008 ;Quirk et al 2004 ;Thompson & Lummis, 2008a ;Van Hooft & Wadman, 2003), but there are also binding sites in other regions of these proteins.…”
Section: Ions As Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations